Environment sensitive hydrogels for drug delivery applications. (November 2019) - Qureshi, Dilshad; Nayak, Suraj Kumar; Maji, Samarendra; Anis, Arfat; Kim, Doman; Pal, Kunal
Graphical abstract: Abstract: Over the last few decades, hydrogels have attracted the considerable interest of researchers for crafting potential controlled drug delivery systems. It may be attributed to their high water imbibing capacity, soft and rubbery nature, which enables them to exhibit physical properties resembling that of the body tissues. Recently, the environment-sensitive hydrogels have received the special attention of the researchers because of the alteration in their properties in response to a stimulus. The special focus on the environment-sensitive hydrogels has facilitated breakthrough advances in drug delivery (e.g., decrease in dose frequency, increase in the duration of release with reduced side effects, ease of preparation and administration) for the better treatment of various pathological conditions. This paper provides comprehensive information regarding the types of stimuli (i.e., physical, chemical and biological) which can be used to stimulate drug release from the hydrogels and recent advances in the development of stimulus-sensitive hydrogels for drug delivery applications. Finally, the current challenges and the future scope of research in the field of environment-sensitive hydrogels have also been highlighted.